LINGUISTIC FEATURES OF THE ARABIC AND PERSIAN ISOPHAS USED IN THE “OLD WORLD (Scientific journal of the Fergana State University, 2023)
This article discusses the Arabic and Persian  izafet,  used in Odil Yakubov's  “Old World”.